Dramatic response to cyclin D–dependent kinase 4/6 inhibitor in refractory poorly differentiated neuroendocrine carcinoma of the breast. Issue 3 (3rd July 2018) - Shanks, Allison; Choi, Julia; Karur, Vinit
ABSTRACT: Neuroendocrine tumors are a rare subset of breast carcinomas. Commonly, platinum-based doublet is used as a systemic treatment option for high-grade neuroendocrine carcinomas from lung, gastrointestinal, and genitourinary origins. In comparison to other breast cancers, neuroendocrine carcinomas have unique genomic features and different treatment strategies. We present a patient with high-grade neuroendocrine carcinoma of the breast who had a successful and durable response to the cyclin D–dependent kinase (CDK) 4/6 inhibitor palbociclib in conjunction with endocrine therapy. This patient was refractory to commonly used platinum-based chemotherapy as well as hormone-based treatment. To date, this is the first published case of use of CDK 4/6 inhibitor in primary neuroendocrine carcinoma of the breast.